The Operations of Exclusion of Immigrated People through Public Policies in Chile - Galaz Valderrama, Caterine; Poblete, Rolando; Frías, Carla (Revista del CLAD Reforma y Democracia, 2017)
In the last 30 years, Chile has become an installation horizon for immigrants, which has been increased since the nineties for several Latin American and Central American countries (Peru, Argentina, Bolivia, Haiti, Colombia and Ecuador). Chile would have some 354,582 migrant’s people who would correspond to approximately 2% of the total population. Nevertheless, the State has developed isolated responses attention to this population that fall into a restricted view of rights, subjected to immigration law in effect since the military dictatorship.For that, it’s necessary to explore the social management of immigration from a thoughtful approach to the notion of “social inclusion/exclusion” considering different normative and social intervener strategies that has been initiated from the public sector to ensure “human rights” of immigrants. For that reason, we’ll present below a reflection about the barriers that are evident in social policies of this country and that is affecting the effective inclusion of the immigrant population, taking into account four main areas: education, housing, employment and health. These results arerom an investigation with a mixed approach (quantitative and qualitative) developed in four geographical areas of Chile with highest immigrant population.Through this investigation we could display that different groups of immigrants in Chile are facing a number of barriers for their effective social inclusion not only derived from socio-cultural apprehensions or a rejection of social community-level reception to the foreign, but also from constraints imposed by the State itself at the level of accessibility to possible benefits. These difficulties are derived from the legislative components that regulate the stay of foreigners in the country, but also occur in administrative terms, the management of programmatic offer available to the State and direct attention given to public services.
Keywords: Immigration Policy; Immigration; Public Policy; Social Policy; Inclusion; Chile